Inpatient prescribing patterns of long-acting injectables and their oral or short-acting injectable equivalent formulations - Liu, Yifei; Patterson, Mark E.; Sahil, Suman; Stoner, Steven C. (Frontiers in Pharmacology, 2023)
BACKGROUND: Long-acting injectable (LAI) antipsychotics (APs) each have an oral equivalent formulation, while aripiprazole, olanzapine, and ziprasidone each also have a short-acting injectable (SAI) equivalent formulation. Inpatient prescribing patterns of LAIs and their oral/SAI equivalents are less characterized in populations other than Medicaid, Medicare, and Veterans Affairs populations. Mapping out inpatient prescribing patterns remains an important first step to ensure appropriate use of antipsychotics during this critical juncture of patient care prior to discharge. This study determined inpatient prescribing patterns of first- (FGA) and second-generation antipsychotic (SGA) LAIs and their oral/SAI formulations. METHODS: This was a large retrospective study using the Cerner Health Facts® database. Hospital admissions due to schizophrenia, schizoaffective disorder, or bipolar disorder from 2010 to 2016 were identified. AP utilization was defined as the proportion of inpatient stays during which at least 1 AP was administered to the total number of inpatient visits over the observed period. Descriptive analyses were used to determine prescribing patterns for APs. Chi-square tests were used to determine utilization differences across years. RESULTS: 94,989 encounters were identified. Encounters during which oral/SAI of SGA LAIs were administered were most common (n=38,621, 41%). Encounters during which FGA LAIs or SGA LAIs were administered were the least common (n=1,047, 1.1%). Prescribing patterns differed across years (p<0.05) within the SGA LAI subgroup analysis (N=6,014). Paliperidone palmitate (63%, N=3,799) and risperidone (31%, N=1,859) were the most frequently administered. Paliperidone palmitate utilization increased from 30% to 72% (p<0.001), while risperidone utilization decreased from 70% to 18% (p<0.001). CONCLUSIONS: Compared with their oral or SAI formulations, LAIs were underutilized from 2010 to 2016. Among SGA LAIs, the prescribing patterns of paliperidone palmitate and risperidone changed significantly.